House Prices, Local Demand, and Retail Prices - Stroebel, Johannes; Vavra, Joseph (Journal of Political Economy, 2019)
We document a causal response of local retail prices to changes in local house prices, with elasticities of 15–20 percent across housing cycles. These price responses are largest in zip codes with many homeowners and are driven by changes in markups rather than local costs. We argue that markups rise with house prices because greater housing wealth reduces homeowners’ demand elasticity, and firms raise markups in response. Shopping data confirm that house price changes affect the price sensitivity of homeowners, but not that of renters. Our evidence suggests a new source of business cycle markup variation.